Continuous haemodynamic monitoring in an unusual case of swallow induced syncope - Deguchi, K. (BMJ Group, 1999)
A 69 year old man is described with a 12 year history of intermittent syncope associated with ingesting solid food, mainly after having fasted. He was taking enalapril, propranolol, bendrofluazide (bendroflumethiazide), omeprazole, finasteride, and aspirin. Detailed investigations, including gastrointestinal evaluation, measurement of various gut hormones, and autonomic testing, indicated no abnormality. A liquid meal, performed before fasting, failed to elicit an episode. However, a solid meal after an overnight fast provoked near-syncope. Continuous non-invasive haemodynamic monitoring (with a Portapres II) indicated a short lived rise in blood pressure and heart rate, followed by severe hypotension, a fall in stroke volume and cardiac output, and then bradycardia. This favoured an initial increase in sympathetic activity, followed by vasodepression due to sympathetic withdrawal or activation of humoral vasodilatatory mechanisms, with bradycardia secondary to impaired cardiac filling. Withdrawal of enalapril abolished the episodes. The unusual nature of this case, in which haemodynamic recordings continuously were made during and after swallow syncope, induced soon after food ingestion, is discussed.